The Use of SDR Transceivers in Systems for Searching Covert Radiodevices - M. A. Bunevich; A. I. Mayorov; I. A. Vrublevsky (Цифровая трансформация)
The paper deals with the construction and design of devices operating by the method of resonance-reflectometric location to discover covert radio devices. The main stages of designing a prototype device operating by the method of resonance-reflectometric location are described. The materials of the analysis of modern types of SDR receivers and their main characteristics are presented. The choice of the SDR transceiver type based on the DDC technology (direct down conversion with frequency) is substantiated, in which the task to digitize the signal from the antenna is performed by the FTP with a high sampling rate. The results of the prototype device studies based on the SDR transceivers to search for covert radio devices are presented. The experimental results confirmed that the characteristics of modern SDR transceivers such as speed, sensitivity, and operating frequency bandwidth is fully consistent with the requirements for the design of resonant-reflectometer locator.